Crosstalk between innate immunity and rumen-fecal microbiota under the cold stress in goats - Luo, Tao; Zhu, Jiangjiang; Li, Kerui; Li, Yongtao; Li, Jun; Chen, Yu; Shi, Hengbo (Frontiers in Immunology, 2024)
The balance of the microbiome, which is sensitive to temperature changes, plays a crucial role in maintaining overall health and reducing the risk of diseases. However, the specific mechanisms by which immunity and microbiota interact to adapt to cold stress have yet to be addressed. In this study, Nanjiang Yellow goats were chosen as a model and sampled during the cold (winter, cold stress) and warm (spring) seasons, respectively. Analyses of serum immune factors, as well as the composition of rumen and fecal microbial communities, were conducted to explore the crosstalk between microbiota and innate immunity under cold stress. Significantly increased levels of IgA (P < 0.01) were observed in the cold season compared to the warm season. Conversely, the levels of IL-2 (P = 0.02) and IL-6 (P < 0.01) diminished under cold stress. However, no significant differences were observed in IgG (P = 0.89), IgM (P = 0.42), and IL-4 (P = 0.56). While there were no significant changes in the diversity of bacterial communities between the warm and cold seasons, positive correlations between serum IgA, IL-2, IL-6 concentrations and several genera were observed. Furthermore, the weighted gene co-expression network analysis indicated that the microbiota enriched in the MEbrown module positively correlated with IgA, while the microbiota enriched in the MEblue module positively correlated with IL-2 and IL-6. The strong correlation between certain probiotics, including Alistipes, Bacteroides, Blautia, and Prevotellaceae_UCG.004, and the concentration of IL-2, and IL-6 suggests their potential role in immunomodulatory properties. This study provides valuable insights into the crosstalk between microbial communities and immune responses under the challenge of cold stress. Further studies on the immunomodulatory properties of these probiotics would contribute to the development of strategies to enhance the stress resistance of animals for improved overall health and survival.